Análisis del proceso de obtención de alcohol extrafino en una destilería - Penín Pérez, Enrique; Albernas Carvajal, Yailet; González Suárez, Erenio; Cervantes Tellez, Yudelsis; Feyt Leyva, Reinier (Centro Azúcar Journal, 2010)
An analysis of the process of obtaining of superfine alcohol is presented in a distillery. Begin with a process description. The aspects analyzed are the mass and energy balances in process, as well as the main water and steam consumers; for these aspects was utilized the Microsoft Excel Program. A simulation of the distiller column is made in order to determine its behavior before possible problems, as the variation of the reflux relationship, as well as the variation in the flow of direct steam that is given to the column; by means of the use of the Hysys Professional Software.